Odpowiedź :
Odpowiedź:
-x+6x =6x2 -2x
5x =6xdo2 -2x
6x do2 -2x =5x
6x do2 -7x=0
x(6x -7)=0
x=o lub x= 7/6
Szczegółowe wyjaśnienie:
[tex]a\\\\\frac{-x }{3x-1} =\frac{ 2x}{1-6x} \\\\3x-1\neq 0\ \ \ \ \ \ 1-6x\neq 0\\\\3x \neq 1\ \ \ \ \ \ -6x\neq -1\\\\ x \neq \frac{1}{3}\ \ \ \ \ \ x\neq \frac{ 1}{6}\\\\D=R\setminus \left \{ \frac{1}{6},\frac{1}{3} \right \}[/tex]
[tex]-x(1-6x)=2x(3x-1)\\\\-x+6x^2=6x^2-2x\\\\-x+6x^2-6x^2+2x=0\\\\x=0[/tex]
[tex]d)\\\\\frac{1}{2}*( 8-\frac{1}{2}x)= 4-\frac{1}{4}x \\\\4-\frac{1}{4}x =4-\frac{1}{4}x\\\\L=P\\\\ rownanie\ jest \ tozsamosciowe,\ nieskonczenie\ wiele\ rozwiazan[/tex]